The role of natural language processing in improving customer service and support in E-Commerce - Kuek, Shu Hui (2023)
This research investigates the factors The study centers on the role of Natural Language Processing (NLP) in improving customer service and support in Ecommerce. The study utilizes quantitative surveys to comprehensively explore the role of Natural Language Processing (NLP) in enhancing customer service and support in E-commerce. Drawing upon a theoretical framework grounded in the Technology of Acceptance Model (TAM) and Social Cognitive Theory(SCT), the research identifies and analyzes key factors such as customer experience, customer satisfaction, perceived ease of use, perceived usefulness, social influence, selfefficacy and observational learning.